KENDALA PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN TAHUN 2023 DESA KARANG SENTOSA KABUPATEN BEKASI - Dahuri, Adin; Yani, Yani (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The reseach presents a description of identifiying and analizing with a qualitative approach regarding the obstacles in collecting Land and Building Tax of Rural and Urban Area (herein after refers to as PBB-P2) periode of 2023 in Karang Sentosa Subdistrict in Bekasi Regency. Data of PBB-P2 achievements sourced from local tax authority and interview conducted with tax officer and some taxpayers. The research shows that achievement rate of PBB-P2 collection in 2023 reached 27% due to contribution of some obstacles such as income decrement due to Covid-19, unoptimal utilization of ceritain alternative places for PBB-P2 payment, and there are also a few landowners who do not reside at Karang Sentosa Subdistrict, and unproportionate number of tax officer compared to taxpayers. Some improvements should be takan to increase the PBB-P2 collection in order to reach its target for the following years. These improvement efforts including conduct ongoing advise for taxpayers to pay their PBB-P2 on time, provides mobile PBB service vehicle stationed at Karang Sentosa Subdistrict office, establishing an intensive collabiration with head of community and neighborhood, and maximalized the utilixation of reguler meeting namely